2011
DOI: 10.1002/fld.2699
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of the kω turbulence model for scramjet flowfield simulations

Abstract: SUMMARY The suitability of Wilcox's 2006 k– ω turbulence model for scramjet flowfield simulations is demonstrated by validation against five test cases that have flowfields representative of those to be expected in scramjets. The five test cases include a 2D flat plate, an axisymmetric cylinder, a backward‐facing step, the mixing of a pair of coaxial jets and the interaction between a shock wave and turbulent boundary layer. A generally good agreement between the numerical and experimental results is obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…The improvements in the 2006 version implemented in Eilmer include: reduced freestream sensitivity, improved behavior for compression corners and hypersonic SWBLI and the capability to handle free shear flows [34]. For this latter model the importance of the stress limiter parameter in predicting separation was demonstrated by Wilcox [34] and confirmed by Chan et al [24] and reasonable agreement with wall pressure data was observed. This version is capable of similar performances as Menter's SST model and the effect of the choice in each solver will be closely observed in the comparison test cases with special attention to separation in SWBLI regions.…”
Section: Eilmer and Hyfoam: Physical And Numerical Modelingmentioning
confidence: 82%
See 2 more Smart Citations
“…The improvements in the 2006 version implemented in Eilmer include: reduced freestream sensitivity, improved behavior for compression corners and hypersonic SWBLI and the capability to handle free shear flows [34]. For this latter model the importance of the stress limiter parameter in predicting separation was demonstrated by Wilcox [34] and confirmed by Chan et al [24] and reasonable agreement with wall pressure data was observed. This version is capable of similar performances as Menter's SST model and the effect of the choice in each solver will be closely observed in the comparison test cases with special attention to separation in SWBLI regions.…”
Section: Eilmer and Hyfoam: Physical And Numerical Modelingmentioning
confidence: 82%
“…The linear eddy viscosity two-equation k − ω turbulence model is the base model for both solvers even if a different variant of it is implemented, and thus available, in each one of them. Eilmer uses Wilcox's 2006 k − ω model [24,34] while hyFoam adopts Menter's Shear Stress Transport (SST) variant [35,36,37]. The two-equation models approach is commonly adopted for hypersonic propulsion CFD [38].…”
Section: Eilmer and Hyfoam: Physical And Numerical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The walls of the inlet and combustor were modeled to be nonslip and to remain at a constant temperature of 300 K. For all simulations conducted, turbulence was modeled using the 2006 k-ω model of Wilcox [44]. This turbulence model has been shown to be suitable for the simulation of the flows in the present experiments [45]. Boundary layers were resolved to the walls with the turbulence model for the Eilmer3 simulations (with a typical y value of 1 for most of the first cells off the walls), whereas boundary layers were modeled to the walls using wall functions for the VULCAN simulations (with a typical y value of about 30 for most of the first cells off the walls).…”
Section: Description Of Computational-fluid-dynamics Simulationsmentioning
confidence: 99%
“…The latest k-ω model was quoted to be less sensitive to turbulence specifications at the freestream and improved performance for the prediction of flow separation for supersonic and hypersonic flows (Wilcox, 2006). The validity of the latest model was investigated by Chan, Jacobs & Mee (2011) for scramjet applications through test cases with expected scramjet flow field representations. The study demonstrated the validity of the model with experimental results for predicting viscous drag and heat transfer distribution for an axisymmetric cylinder model with a Mach 9 flow.…”
Section: Turbulence Modelmentioning
confidence: 99%